Turkish language proficiency and cultural adaptation of American EFL teachers in Turkey - Şahan, Özgür; Şahan, Kari Elizabeth; Razi, Salim (Elsevier Science Bv, 2014)
Intercultural competence is needed for effective and appropriate intercultural interactions. However, differences between individuals and specific factors, such as directness/indirectness and collectivism/individualism, should be considered when examining cultural adaptation. This paper aims to reveal the possible effects that language proficiency has on cultural adaptation. Although the 31 American teachers surveyed in this study had different levels of Turkish language proficiency, the results indicated no significant differences between their language proficiency and sociocultural adaptation. However, a significant negative correlation was found between previous experience abroad and successful sociocultural adaptation in Turkey. The main conclusion of this study questions the relationship between traditional conceptions of language proficiency and successful sociocultural adaptation. (C) 2014 The Authors. Published by Elsevier Ltd.
14th Language, Literature and Stylistics Symposium -- OCT 15-17, 2014 -- Selcuk, TURKEY
Keywords: sociocultural adaptation; Turkish language proficiency; intercultural interaction; intercultural competence; unfamiliar cultures